Undergraduate nursing students’ preferences for virtual reality simulations in nursing skills training: A discrete choice experiment - Yanya Chen; Yan He; Xiaochun Zou; Hongya Cai; Hei Hang Edmund Yiu; Wai-kit Ming (Digital Health)
Objective Nursing students face increasing challenges, making it crucial to explore innovative teaching methods such as virtual reality simulations to enhance skills. This study aimed to assess their preferences for virtual reality simulation in skills training using a discrete choice experiment. Method A discrete choice experiment with six attributes (types of virtual reality, interaction, learning contents, collaboration, frequency, and costs for each additional training module) was used. A mixed logit model and latent class analysis were adopted to analyze data using Sawtooth Software and STATA BE 18. Result A total of 518 undergraduate nursing students completed this study. They identified costs for each additional training module, interaction, and types of virtual reality as the three most important attributes. The combination that was most preferred was immersive virtual reality simulation, high-level interaction types, advanced learning contents, mixed learning modules, lower prices, and a practice frequency of once every two weeks. Two classes of students were identified: Class 1 valued the cost for each additional training module, while Class 2 preferred a better immersion experience. Conclusion Students’ preference for virtual reality simulation depended on some factors, including types of virtual reality, interaction, learning contents, and costs for each additional training module. Nursing educators should take students’ preferences into account to ensure that their preferences and needs are addressed as fully as possible.